2019
DOI: 10.1177/2325967119868212
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Covered Autologous Chondrocyte Implantation Versus Autologous Matrix-Induced Chondrogenesis: A Randomized Trial Comparing 2 Methods for Repair of Cartilage Defects of the Knee

Abstract: Background:Autologous matrix-induced chondrogenesis (AMIC) is a single-stage alternative to autologous chondrocyte implantation for treatment of localized cartilage defects of the knee. To our knowledge, no randomized controlled trial exists comparing the 2 methods.Purpose:To evaluate any difference in the outcome of AMIC as compared with collagen-covered autologous chondrocyte implantation (ACI-C).Study Design:Randomized controlled trial; Level of evidence, 2.Methods:A prospective randomized controlled clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 38 publications
3
52
1
Order By: Relevance
“…Specific to ACI in comparison with AMIC, both procedures show comparable outcomes. 10 Although this was a fairly small study, with only 21 ACI patients and 20 AMIC patients, it seems that either treatment can achieve positive outcomes for patients.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Specific to ACI in comparison with AMIC, both procedures show comparable outcomes. 10 Although this was a fairly small study, with only 21 ACI patients and 20 AMIC patients, it seems that either treatment can achieve positive outcomes for patients.…”
Section: Discussionmentioning
confidence: 85%
“…Some of these were previously mentioned by Gao et al, 12 who pointed to the need for further high-level studies. Although the recent data that were presented by Fossum et al 10 would certainly meet the criteria for a level 1 study, the use of data from a registry such as ours should not be discounted. The use of a registry provides real-world data among a diverse patient population, although this limits data collection because follow-up visits adhere to standard of care, whereas prospective studies will have predefined data collection points.…”
Section: Discussionmentioning
confidence: 87%
“…Adult cartilage has a limited regenerative capability due to its unique structure as it is avascular, aneural, and alymphatic 1 . Autologous chondrocyte implantation (ACI) and matrix-assisted autologous chondrocyte implantation (M-ACI) are the most promising cell-based treatments to treat cartilage defects 2 4 . In both procedures, chondrocytes are retrieved from patients’ own cartilage, serially expanded in vitro, and re-implanted into the patients’ defective site 2 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of matrix cellebased cell therapy was reported by Brittberg et al 58 to result in superior outcomes at 5-year follow-up compared with patients undergoing microfracture alone for symptomatic cartilage knee defects !3 cm 2 . Moreover, Fossum et al 59 reported significant improvements in clinical outcomes at 2 years in patients with symptomatic chondral or osteochondral defects (>2 cm 2 ) of the distal femur or patella treated with autologous matrix-induced chondrogenesis (AMICÒ) or collagen-covered autologous chondrocyte implantation (ACI-C). Volz et al 60 reported significant functional improvement at 5 years in patients with isolated cartilage defects (2 to 3 cm 2 ) of the knee located on the medial or lateral femoral condyle, trochlea, or patella treated with AMIC using a type I/III collagen membrane compared with microfracture alone.…”
Section: Matrix Cellebased Therapymentioning
confidence: 99%